1982
DOI: 10.1093/oxfordjournals.jbchem.a133872
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Clam-Foot Paramyosin, Tropomyosin, and Rabbit Skeletal Light-Meromyosin on the ATPase and Superprecipitation Activities of Actomyosin1

Abstract: 1. Clam-foot paramyosin strongly inhibited superprecipitation of clam-foot actomyosin whereas it did not at all affect its ATPase reaction. On the other hand, superprecipitation of rabbit actomyosin and its ATPase reaction were both inhibited by clam foot paramyosin. 2. Clam-foot paramyosin did not at all affect the Mg-ATPase activity of clam-foot myosin alone (with no actin) but inhibited that of rabbit skeletal myosin alone. 3. Clam-foot paramyosin did not affect the ATPase reaction of rabbit acto-clam myosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A large number of papers deal with isolation and initial characterization (e.g., Ca ++ and ATP dependence, heavy and light chain complement) of molluscan actomyosin (Lajtha, 1947;Humphrey, 1948Humphrey, , 1949Weber, 1953;Matsumoto, 1954, 1957;Weber and Portzehl, 1954;de Villafranca, 1955;Tonomura et al, 1955Tonomura et al, , 1956Bailey, 1956;Strelina et al, 1957;Matsumoto, 1957;Maruyama, 1957bMaruyama, , 1958aMatsumoto, 1958aMatsumoto, -d, 1959Kishimoto, 1961;Bárány and Bárány, 1966;Schädler, 1967;Mognoni and Lanzavecchia, 1969;Twarog and Muneoka, 1972;Horie et al, 1975;Azuma et al, 1975;Azuma, 1976;Nishita, 1977;Nishita et al, 1977Nishita et al, , 1979Tsuchiya et al, 1978b-d;Asada et al, 1979;Toyo-Oka, 1979;Tanaka and Tanaka, 1979a,b;Ashiba et al, 1980Ashiba et al, , 1982Kimura et al, 1980;Asakawa, 1980;Stephenson and Williams, 1980;Morita and Kondo, 1982;Szent-Györgyi and Niebieski, 1982;Yoshitomi and Konno, 1982;Krause and Munson, 1982;Kodama and Konno, 1983...…”
Section: 411mentioning
confidence: 99%
“…A large number of papers deal with isolation and initial characterization (e.g., Ca ++ and ATP dependence, heavy and light chain complement) of molluscan actomyosin (Lajtha, 1947;Humphrey, 1948Humphrey, , 1949Weber, 1953;Matsumoto, 1954, 1957;Weber and Portzehl, 1954;de Villafranca, 1955;Tonomura et al, 1955Tonomura et al, , 1956Bailey, 1956;Strelina et al, 1957;Matsumoto, 1957;Maruyama, 1957bMaruyama, , 1958aMatsumoto, 1958aMatsumoto, -d, 1959Kishimoto, 1961;Bárány and Bárány, 1966;Schädler, 1967;Mognoni and Lanzavecchia, 1969;Twarog and Muneoka, 1972;Horie et al, 1975;Azuma et al, 1975;Azuma, 1976;Nishita, 1977;Nishita et al, 1977Nishita et al, , 1979Tsuchiya et al, 1978b-d;Asada et al, 1979;Toyo-Oka, 1979;Tanaka and Tanaka, 1979a,b;Ashiba et al, 1980Ashiba et al, , 1982Kimura et al, 1980;Asakawa, 1980;Stephenson and Williams, 1980;Morita and Kondo, 1982;Szent-Györgyi and Niebieski, 1982;Yoshitomi and Konno, 1982;Krause and Munson, 1982;Kodama and Konno, 1983...…”
Section: 411mentioning
confidence: 99%
“…Ashiba et al,10) found that the Mg-ATPase acti vity of clam foot myosin alone is as sensitive as that of skeletal acto-clam foot myosin, and that the desensitization of clam foot myosin is accompanied by the reversible loss of superprecipitation activity of the actomyosin. From these findings, they proposed that the primary role of the regulatory light chain in Call-regula tion is to inhibit myosin ATPase activity not actin-myosin interaction, and the secondary role is to maintain the conformation of myosin heads which is essential for actin-myosin inter action.11) Thereafter, these findings were confirmed with myosins from squid Todarodes pacifzcus,12) ezo-giant scallop, 12) akazara scallop, [13][14][15][16][17] and surf-clam Spisula sacharinen sis,18) and extended to the tension development …”
mentioning
confidence: 99%
“…While associated, the muscle is able to maintain the developed tension. However, Nonomura (1974) as well as Ashiba et al (1982) were unable to confirm the observations made by Szent-Gyorgyi et al (1971). Instead, they showed that the paramyosin slightly enhances the Mg-ATPase activity rather than inhibiting it.…”
Section: Phenomenon;mentioning
confidence: 58%
“…This research group, however, did not specify the clam species used in their study. Recently, Konno et al (1988), using squid (Todarodespacijicus), reported that they could not confirm the findings of Ashiba et al (1982) that the effect of paramyosin on the ATPase activity depends on the source of myosin. As one must note, the observations of Szent-Gyorgyi et al (1971), Nonomura (1974), Ashiba et al (1982) and Konno el al.…”
Section: Phenomenon;mentioning
confidence: 97%
See 1 more Smart Citation